ANALISIS PERBEDAAN KADAR β-KAROTEN PADA UBI JALAR KUNING (Ipomoea batatas L.) MENTAH DAN REBUS DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Cut Bidara Panita Umar; Jamila F Kabakoran; Dewi Sukma Hukom (Lembaga Pengembangan Kinerja Dosen, 2022)
Sweet potato is a good food ingredient, because of its starch which has a very rich nutritional content, including high carbohydrates. Therefore, in some areas sweet potato is also used as a staple food. It also contains protein, vitamin C and is rich in vitamin A (β-carotene). β-carotene in yellow sweet potato (Ipomoea batatas L.) can function to meet the needs of vitamin A and as an antioxidant in reducing the effects of free radicals. The purpose of this study was to determine the differences in β-carotene levels in raw and boiled yellow sweet potato (Ipomoea batatas L.) using the UV-Vis spectrophotometry method. Samples of yellow sweet potato were extracted by using maceration method with 95% ethanol solvent. Then a quantitative analysis was performed using the UV-Vis spectrophotometry method at a wavelength of 450 nm and a linear regression equation was obtained y = 0.0237x + 0.395 and a correlation coefficient (r) of 0.9931 and an average level of β-carotene in raw yellow sweet potato was obtained of 1278 .23 mg/kg and boiled yellow sweet potato of 413.90 mg/kg. So from this study it can be concluded that the levels of β-carotene in raw yellow sweet potatoes are greater than boiled yellow sweet potatoes because some boiled yellow sweet potatoes have been damaged due to heat or dissolved / lost to water.